RETRACTED: Interaction between universities and forestry enterprises for the development university ecosystems in Russia - Kravchenko Pavel; Burtsev Daniil; Gavrilyuk Elena; Izotova Anna; Litvinova Natalia (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001